(untitled) (Green Life Medical College Journal, 2025)
Introduction: Acute kidney injury is an important public health problem in patients treated with gentamicin. Kalmi shak and ramipril have nephroprotective effects that can alleviate gentamicin induced nephrotoxicity. A study was carried out on a group of rats to evaluate the nephroprotective effects of kalmi shak and ramipril with their comparison. Methods: An experimental study was conducted to demonstrate the effects of ethanolic extract of kalmi shak and ramipril on blood urea and serum creatinine levels as well as histopathological changes in gentamicin induced nephrotoxic rats and the nephroprotective effects were compared with kalmi shak and ramipril respectively. Results: Blood urea and serum creatinine levels were significantly higher than the normal in gentamicin treated group. There were significant differences in blood urea and serum creatinine levels as well as histopathological changes in gentamicin to kalmi shak and ramipril treated groups. Another test revealed no significant differences in blood urea and serum creatinine levels as well as histopathological changes between the kalmi shak and ramipril treated groups. Nephroprotective effects were observed with ethanolic extract of kalmi shak which was almost similar to that of ramipril. Conclusion: Kalmi shak and ramipril have nephroprotective effect that can alleviate gentamycin induced nephrotoxicity which is comparable to each other, though exact mechanism could not be confirmed by this study. Journal of Green Life Med. Col. 2025; 10(2): 41- 46